PRESERVATION OF PROTEINACEOUS MATERIAL DURING THE DEGRADATION OF THE GREEN ALGA BOTRYOCOCCUS BRAUNII: A SOLID-STATE 2D 15N 13C NMR SPECTROSCOPY STUDY - Zang X.; Nguyen R.T.; Harvey H.R.; Knicker H.; Hatcher P.G. (My University, 2001)
Using solid-state cross-polarization-magic-angle-spinning (CPMAS) 13C and 15N nuclear magnetic resonance (NMR) and 2-D double cross polarization (DCP) MAS 15N 13C NMR techniques, microbially degraded Botryococcus braunii was analyzed to study the chemical nature of organic nitrogen in the algal residue. The amide linkage, as found in protein, was observed as the major nitrogen component in 201-day-old degraded algae. No significant amount of heterocyclic nitrogen, or evidence for melanoidin products, was found. The results strongly suggest that proteinaceous material can survive early diagenesis and be preserved via its encapsulation by refractory, macromolecular, organic matter.